Assessment of Biosafety Practices and Occupational Risks in Biomedical Laboratories in Kinshasa, Democratic Republic of Congo. - Diane Sare Gamani; Richard Ekila Ifinji; Placide Ngandu Cyanga; Aliocha Natuhoyila Nkodila; Gertrude Mongila Matimada; Lydie Hamunaki Masika; Bel-Ange Birhaheka; Patience Paty Moloko Maindo; Jérémie Masidi Muwonga (International Journal of Endorsing Health Science Research, 2025)
Background: Biosafety is a critical component in protecting human, animal, and environmental health. However, its implementation in biomedical laboratories across low-resource countries remains limited. This study aimed to assess the current state of biosafety practices in biomedical laboratories in Kinshasa and to identify factors associated with occupational exposure to blood-borne pathogens. Methodology: An analytical cross-sectional survey was conducted between 1st February and 30th May 2025 in 51 biomedical laboratories across the four districts of Kinshasa. Data were collected through direct observations, semi-structured interviews, and structured questionnaires administered to 290 laboratory staff. Variables assessed included laboratory infrastructure, biosafety measures, staff training, and occupational exposure history. Results: The majority of laboratories were peripheral (80.4%) and public sector facilities (66.7%). Only 33.3% of laboratories met the defined biosafety quality criteria, with handwashing stations being the most common element (98%) and staff vaccination the least (11.8%). Among the 290 participants, most were male (57.2%), aged 30–39 years (34.5%), and university educated (98.3%). Nearly half (47.9%) reported occupational exposure to blood, yet only 20.3% underwent testing and 18.8% sought medical consultation. Logistic regression identified age ≥30 years (aOR 1.85–2.81), professional experience >10 years (aOR 2.24–2.85), and lack of biosafety training (aOR 3.19, 95% CI: 2.27–5.96) as independent predictors of exposure. Conclusion: Biosafety in Kinshasa biomedical laboratories remains inadequate, with major deficiencies in training, infrastructure, and post-exposure management. Strengthening biosafety systems through regular audits, continuous training, and policy enforcement is urgently required to reduce occupational risks and improve laboratory safety.